The Relationship Between Perceptions of Taxation Sanctions and Tax Compliance of PBB Taxpayer in Kelurahan Duri Pulo. - Dwi Asri Julianita; Ati Sumiati (Jurnal Ilmiah Wahana Akuntansi, 2016)
This research was aimed to obtain valid and reliable data about The Relationship Between The Perception of the Tax Penalty and Tax Compliance on Taxpayer Land and Building Tax at Duri Pulo Villages Jakarta. This research was conducted by survey method with correlational approach. This research was conducted on February to December 2014. The population in this research were all taxpayer. Affordable population in this research were taxpayer land and building tax, amount to 71 persons. Total of samples used were 58 persons research. Sampling technique used simple random sampling. The result from this study partial and simultaneous testing of consciousness there significantly influence to tax penalty and Tax Compliance on Taxpayer Land and Building Tax. Keywords: Tax Penalty, Tax Compliance